Larval and pupal descriptions of Anomalini (Coleoptera: Scarabaeidae: Rutelinae) species from Ecuador - Filippini, Valentina; Onore, Giovanni; Guidolin, Laura (Zootaxa, 2017)
The third instars are described and illustrated for five Anomalini (Coleoptera: Scarabaeidae: Rutelinae) species from Ecuador: Anomala balzapambae Ohaus, 1897, A. popayana Ohaus, 1897, A. valida Burmeister, 1844, Callistethus buchwaldianus (Ohaus, 1908), and C. levii (Blanchard, 1851). The pupae of three Ecuadorian species are also described and illustrated: A. discoidalis Bates, 1888, A. popayana, and C. levii. Diagnostic characters of the species are provided. A key to the known larvae of Anomalini from the New World is provided, which now includes five genera and 31 species.